Oral desmopressin in neonatal diabetes insipidus. - Stick, S M (1987)
A neonate with cranial diabetes insipidus was successfully treated with oral desmopressin. The patient had a midline cleft lip and palate and we obtained a more consistent response using the oral route than using the usual nasal route.